Managing As Mission : Nonprofit Managing for Sustainable Change - Heninger, Lori (Boca Raton, FL : CRC Press, 2017)
"Managing As Mission pushes the boundaries of what it means to be a nonprofit manager by making the case that managing as a reflection of the organizational mission - the cornerstone of any nonprofit - can bring about the change nonprofits were created to achieve: a better world for all. The book contains real-world examples, interview excerpts from nonprofit managers and directors, and a series of self-reflection and organization-wide tools to develop managers and managing as a mirror of the mission. Themes within the book include: a discussion of the history of nonprofit missions; management scope, tasks and approaches as well as values, relationship and trust; and creating organizational structures and interactions that mirror the organizational mission. This book is crafted from interviews with nonprofit managers and directors and the writings of Martin Buber, Peter Drucker, Shalom Schwartz and others. It also includes exercises to help nonprofit managers successfully manage as mission. The book is written in an informal first-person style, utilizing humor that will allow the reader to see themselves in the examples and stories."--Provided by publisher.
Chapter 1 Why Managing As Mission? -- chapter 2 The Mission -- chapter 3 Process -- chapter 4 Managing -- chapter 5 Linking Managing, Mission, and Process -- chapter 6 What Can Come from Managing As Mission -- chapter 7 Tools.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS -- Production & Operations Management; POLITICAL SCIENCE -- Public Affairs & Administration; Nonprofit organizations -- Management; Leadership